Digital feasibility of yaka photo & studio as an msmes in the non-urban creative industry - Surahman Surahman; Rahmawati Idha Wibowo; Septiani Anggun Dwiyanti; Lutfita Syifa Agriyanti; Fendi Indra Wardana (Enrichment : Journal of Management, 2025)
This study evaluates the feasibility of Yaka Photo & Studio in Tenggarong Seberang District from market, technical, and financial perspectives. The research is important due to the rising demand for photography services in non-urban areas, where many businesses operate without proper feasibility assessments, creating risks of financial loss and missed opportunities. A descriptive mixed-method approach is applied. Market analysis identifies target consumers and potential demand; technical analysis reviews location, facilities, and operational readiness; and financial analysis uses Net Present Value (NPV), Internal Rate of Return (IRR), payback period, and break-even indicators. The results show a strong market outlook with high demand and low competition. Technically, the business benefits from a strategic location, adequate equipment, and experienced staff that support smooth operations. Financially, the business is feasible, evidenced by a positive NPV of IDR 141,464, an IRR of 10% exceeding the 8% discount rate, a 2.3-year payback period, and a BEP of 61%, which remains below the general feasibility threshold of around 70%. These findings enrich the literature on non-urban creative industries and highlight the relevance of digital marketing. Practically, the results offer guidance for local entrepreneurs in improving digital promotion and assessing financial feasibility for sustainable development